Interference of Speakers in Arabic Podcast: Darunnajah 6th Language Competition Arabic For Boys – Darunnajah 8 - Izzat Fathin Hannawi; Nurlinah Nurlinah; Rohanda Rohanda (Green Publisher Indonesia, 2025)
In the process of learning Arabic for students in Islamic boarding schools, as our mother tongue is Indonesian, of course there is language contact which causes variations in language, even to the point of interference. Therefore, this research was conducted with the aim of analyzing (1) the forms of language interference in the speakers in the podcast Darunnajah 6th Language Competition Arabic for Boys on the on the Darunnajah 8 Official Youtube channel, (2) Analyzing the factors that cause language interference in the speakers. The approach to this research is descriptive qualitative. The method used is the method of listening freely, engaging in conversation through podcasts on the Darunnajah 8 Official YouTube media and taking notes to obtain appropriate data which is then analyzed using the agih method with the technique for direct elements (BUL) to describe the form of language interference in the speakers in the Darunnajah 6th Language Competition podcast. Arabic for Boys on the Darunnajah 8 Official Youtube channel. Apart from that, this research also uses the matching method with the determining element selection (PUP) technique to describe the factors that cause language interference among speakers. The results of this research (1) there were 40 cases of interference language which consists of interference in the form of phonology, language interference in the form of morphology, and language interference in the form of syntax (2) the factors causing language interference are the students' bilingualism, the existence of differences system between B1 and B2, and the influence of dialect.